Penerapan Algoritma Apostolico-Giancarlo dalam Sistem Sharing Knowledge Sebagai Upaya Meningkatkan Kompetensi Pegawai - Puspita, Fanny Tania Ghia; Nur Wulan; Yessi Fitri Annisah Lubis (Jurnal Mahajana Informasi, 2024)
Knowledge Management is an effort made to manage knowledge through three important components, namely, people, processes and technology. The knowledge contained in each individual that is still stored in the head (tacit knowledge) needs to be documented in a media or system (explicit knowledge) so that intellectual assets in the organization are maintained. In line with the mission of the Ministry of Finance, namely adaptive management of Human Resources according to technological advances, the linkage and compatibility between education, learning and application of values ​​and performance targets supported by knowledge management has been realized. The Information and Communication Technology and State Property Management Office is a Technical Implementation Unit which is under and directly responsible to the Head of the Center for Information Systems and Financial Technology, Secretariat General, Ministry of Finance. Knowledge management must be managed well to increase employee competency by using the Apostolico-Giancarlo algorithm search method through the Knowledge Management System.